Study of depot medroxyprogesterone acetate as an extended postpartum contraceptive at SCB medical college and hospital, Cuttack - Samal, Sagarika; Das, Lucy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Increase in contraceptive use during the postpartum period substantially reduces the rate of maternal and infant mortality by preventing unplanned and unwanted pregnancies. Injectable Medroxy Progesterone acetate (DMPA) is one long acting reversible safe and effective method for postpartm contraception. Aims and Objectives to study the acceptance, efficacy, side effects and compliance of DMPA as an extended postpartum contraceptive at SCB Medical College, Cuttack. Methods: The study includes 76 women between 6weeks to 1year postpartum who had chosen DMPA as contraceptive after counseling regarding the basket of choices. DMPA injection was given within 7 days of menstruation if it has returned or at any time after being confirmed that woman is not pregnant with a back up for first 7days. Subsequent injections were given at three monthly intervals and followed up for one year after the first injection for pregnancy rate, side-effects, discontinuation and patient satisfaction. Results: Maximum females were from the combined age groups 25-29 (39.47%) and 20-24 years (35.52%). 46.1% women belong to lower middle socioeconomic group. The most common menstrual problem was amenorrhea in 47.36% followed by scanty bleeding in 22.36%. 25% discontinued after 1st dose of injection, which is the maximum. The commonest reason for discontinuation observed was menstrual problems (37.93%) followed by use of other methods of contraception (17.24%). Out of 76, 23 women were not satisfied (30.26%), main reason of dissatisfaction being menstrual problems. Failure rate was nil. Conclusions: The study concludes that DMPA is a very effective, safe, and long acting contraceptive with no effect on lactation. Proper counseling can improve the acceptance and compliance.